COMPATIBILITY OF CERTAIN INSECTICIDES AND FUNGICIDES IN THE MANAGEMENT OF SUCKING PESTS AND LATE LEAF SPOT IN GROUNDNUT - KUMAR, G. V. SUNEEL (The Journal of Research, PJTSAU, 2019)
Six insecticides and two fungicides at recommended concentrations were evaluated as tank mix in various insecticide and fungicide combinations for their efficacy against sucking insects pests viz., thrips, leafhopper and late leaf spot in groundnut during Kharif 2014. Slight phytotoxic (chlorosis) symptoms were seen in combination treatments of imidacloprid + mancozeb + carbendazim and monocrotophos + mancozeb + carbendazim with phytotoxicity score of 1 (0 to 10%) only at recommended dose. The chemical compatibility of insecticide and fungicide combinations measured through the bio-efficacy studies under field conditions revealed that the insecticides, spinosad and thiomethaxam were effective against thrips; thiomethaxam and acetamiprid were effective against leafhopper and their combination with fungicides in no way undermined the efficacy when mixed indicating their compatibility. Similarly the fungicides, mancozeb and carbendazim registered the same efficacy with respect to late leaf spot disease (31-40% disease severity) alone and in combination with other insecticides. The dry pod yields are also highest in insecticide and fungicide combinations (578.7 to 1064.8 kg ha-1) compared to insecticides (555.6 to 995.4 kg ha-1) or fungicides alone (486.1 to 532.4 kg ha-1) and untreated control (416.7 kg ha-1). Thus all the insecticides and fungicides used in the present investigation are compatible with each other and can be combined as tank mix for control of groundnut pests.